2019
DOI: 10.1016/j.ijid.2019.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 CYP2B6*6 distribution among Congolese individuals with HIV, Tuberculosis and Malaria infection

Abstract: A total of 418 patients with HIV-1 mono-infection, HIV-1 and Tuberculosis coinfection and symptomatic P. falciparum malaria were genotyped for the CYP2B6 c.516G>T SNP using Restriction Fragment Length Polymorphism (RFLP). The allele frequencies and genotype distributions were determined. Results: The CYP2B6 c.516G>T was successfully analysed in 69% (288/418) of the study participants. Among the investigated individuals, the distribution of the major allele CYP2B6*G was 45% and the minor CYP2B6*T allele was 55%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Notably, there is intraethnic variability in the occurrence of CYP2B6 polymorphisms in a given population. For instance, the frequency of CYP2B6*9 varies from 20% in South African Xhosa, 25% in the Congolese to 37% in the Cameroonian population 124–126 . Meanwhile, CYP2B6*6 varies from 22% in the Tswana of Botswana, 34% in the Kenya Kikuyu to 42% in the Nigerian Yoruba population 127,128 .…”
Section: The Impact Of Cytochrome P450 Modulators On the Pharmacokine...mentioning
confidence: 99%
“…Notably, there is intraethnic variability in the occurrence of CYP2B6 polymorphisms in a given population. For instance, the frequency of CYP2B6*9 varies from 20% in South African Xhosa, 25% in the Congolese to 37% in the Cameroonian population 124–126 . Meanwhile, CYP2B6*6 varies from 22% in the Tswana of Botswana, 34% in the Kenya Kikuyu to 42% in the Nigerian Yoruba population 127,128 .…”
Section: The Impact Of Cytochrome P450 Modulators On the Pharmacokine...mentioning
confidence: 99%
“…Several clinical studies on African populations ( Table 1 ) have demonstrated the potential for PGx testing and dose adjustments in HIV patients receiving Efavirenz [ 26 , 27 , 28 , 30 , 41 , 42 ]. Other clinical studies have identified PGx biomarkers for African patients receiving rosuvastatin [ 43 ], imatinib [ 44 ], anti-retroviral (ARV) therapy, TB, and antimalarial comedication [ 25 , 45 , 46 , 47 ]. Importantly, a clinical study has demonstrated associations between genetic variants and clinical responses among Hepatitis C virus-infected patients from SSA and Europe treated with pegylated interferon-alpha/ribavirin [ 48 ].…”
Section: Paucity Of Clinical Pharmacogenetics Studies In Ssamentioning
confidence: 99%
“…In Europe, the distribution is G: 76.8%, T: 23.2%, in the United States of America it is G: 63.8%, T: 36.2% and in Africa, which has the highest prevalence of the polymorphism, it is G: 65%, T: 35% (Scibona et al, 2015). The prevalence of TT genotype of Burkinabe population was 18%, which is different of its frequency in congolese population (28%) (Peko et al, 2019). The South African study revealed the prevalence of the allelic variant CYP2B6 TT (poor metabolisers) to be 23% amongst their study population (Gounden et al, 2010).…”
Section: Discussionmentioning
confidence: 86%
“…The function of cytochrome P450 (CYP) enzymes, one of the major catalysts in drug metabolism, is significantly influenced by genetic polymorphisms leading to substantial inter-individual variability in drug response and/ or adverse reactions activity (Adzu et al, 2014;Eziah et al, 2016;Peko et al, 2019;Oseni et al, 2019;Hashemi-Soteh et al , 2021;Mango et al, 2022). Although human CYP2B6 constitutes only 1-4% of hepatic CYP protein content, it is responsible for the metabolism of some clinically important drugs, including the antidepressant bupropion, the antiretroviral efavirenz, the anticancer cyclophosphamide, the analgesic ketamine and methadone1-4.…”
Section: Introductionmentioning
confidence: 99%